Effect of pre-damage induced by argon ions on the deuterium blister formation in tungsten-tantalum alloys exposed to deuterium plasma. (30th August 2019) - Zhou, Hang; Yu, Jiangang; Chen, Changan; Zhu, Kaigui
Abstract: This work aims to investigate the effects of 800 keV argon ions pre-damage on the following deuterium plasma irradiation behavior in tungsten-tantalum alloy (5 wt% tantalum dopant). The un-damaged and pre-damaged W–5%Ta were exposed to 60 eV deuterium plasma at a fluence of 1.944 × 10 26 D/m 2 in the linear plasma device. The results suggest that pre-damaged induced by Ar 8+ ions can effectively mitigate deuterium-induced blistering, while the deuterium retention is significantly higher as compared to the un-damaged W–5%Ta. According to the transmission electron microscopic (TEM) analysis, a large number of defects can be observed clearly after irradiation by 800 keV Ar 8+ ions, such as vacancies and dislocation loops, which eventually affect the surface blistering and deuterium retention in W–5%Ta. Furthermore, we also compared the deuterium retention in pre-damaged pure W, which was significantly increased by a factor of 15 than in pre-damaged W–5%Ta. Highlights: Pre-damages induced by Ar 8+ ions can effectively mitigate deuterium-induced blistering in W-5%Ta. Higher deuterium retention within the range of 300–1200 K in the pre-damaged W-5%Ta. The damages induced by Ar 8+ ions can lead to the irradiation harden of W-5%Ta. The deuterium retention in pre-damaged pure W was increased by a factor of 15 than in pre-damaged W-5%Ta.